An Overview of Pentatricopeptide Repeat (PPR) Proteins in the Moss Physcomitrium patens and Their Role in Organellar Gene Expression - Mamoru Sugita (Plants, 2022)
Pentatricopeptide repeat (PPR) proteins are one type of helical repeat protein that are widespread in eukaryotes. In particular, there are several hundred PPR members in flowering plants. The majority of PPR proteins are localized in the plastids and mitochondria, where they play a crucial role in various aspects of RNA metabolism at the post-transcriptional and translational steps during gene expression. Among the early land plants, the moss Physcomitrium (formerly Physcomitrella) patens has at least 107 PPR protein-encoding genes, but most of their functions remain unclear. To elucidate the functions of PPR proteins, a reverse-genetics approach has been applied to P. patens. To date, the molecular functions of 22 PPR proteins were identified as essential factors required for either mRNA processing and stabilization, RNA splicing, or RNA editing. This review examines the P. patens PPR gene family and their current functional characterization. Similarities and a diversity of functions of PPR proteins between P. patens and flowering plants and their roles in the post-transcriptional regulation of organellar gene expression are discussed.